Hubungan Antara Profil Dermatoglifi Mahasiswa Penderita Asma Dengan Indeks Prestasi Mahasiswa (IPK) - Yenni Zulhamidah; Kencono Viyati; Kinasih Prayuni; Etty Widayanti; Endang Purwaningsih; Restu Samsul Hadi; Mirfat Mirfat (Jurnal Kesehatan, 2021)
Asthma is a respiratory disease caused by narrowing of the bronchial tubes, causingshortness of breath. Asthma is a multi-factorial disorder resulting from a combination ofgenetic and environmental factors. Asthma impact on productivity because most of patientsexperiencing symptoms that affect their daily lives. Dermatoglyphs, patterns of skin ridges,are derived from the hypodermal neural system and formed embryologically between the10th and 17th weeks. Student productivity can be measured by the Grade Point Average(GPA). In this study we determine the dermatoglyphic profile and the relationship betweenasthma and student’s GPA. Dermatoglyphic prints were obtained from both hands of 57students with asthma and 28 students without asthma. The frequency of GPA and fingerpatters calculated directly using Excel sheet. The association of GPA, student finger patternsand asthma calculated using Chi-Square. The results showed that the distribution of fingerpatterns among students with asthma is 38% whorl, 4% arch and 59% loop, whereas thefinger patterns among students without asthma is 32% whorl, 7% arch and 61% loop. Thesedata show that the finger pattern of the most asthmatic students is whorl compared tostudents without asthma. There are no significant association between the finger patternswith asthma. Students with asthma is relatively lower in GPA (<3) than students withoutasthma. Further analysis showed that students with lower GPA (< 3) significantly associatedwith asthma. Based on present study, it showed that the student productivity is low in studentwith asthma than student without asthma. However, there are no significant differentbetween GPA of students with asthma and students without asthma. Moreover, our findingscannot be generalized as our study had a small sample size. Hence, more elaborate studieswith larger samples with student’s relatives data worth to be done to get conclusive answerson whether dermatoglyphics can be used to predict productivity of student with asthma basedon their GPA.